2016
DOI: 10.1007/s40830-016-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Neutron Diffraction Study of NiTi–21Pt High-Temperature Shape Memory Alloys

Abstract: In situ neutron diffraction was used to investigate the microstructural features of stoichiometric and Tirich NiTiPt high-temperature shape memory alloys with target compositions of Ni 29 Ti 50 Pt 21 and Ni 28.5 Ti 50.5 Pt 21 (in atomic percent), respectively. The alloys' isothermal and thermomechanical properties (i.e., moduli, thermal expansion, transformation strains, and dimensional stability) were correlated to the lattice strains, volume-averaged elastic moduli, and textures as determined by neutron diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Moreover, solid solution strengthening was also found to improve high temperature strength of Ti50Pt50 alloy [1][8][9] [10]. Previous studies reported that, partial substitution of Pt with Ni, Ti50Pt21Ni29 and Ti50.5Pt21Ni28.5 alloys, showed an improved work output and reduced transformation temperatures (Af less than 500 • C) [11] when compared to Ti50Pt50 alloy. However, partial substitution of Ni with Pt in TiNi alloys results in high temperature transformation properties and the ability to perform work under relatively high stress conditions at high temperatures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, solid solution strengthening was also found to improve high temperature strength of Ti50Pt50 alloy [1][8][9] [10]. Previous studies reported that, partial substitution of Pt with Ni, Ti50Pt21Ni29 and Ti50.5Pt21Ni28.5 alloys, showed an improved work output and reduced transformation temperatures (Af less than 500 • C) [11] when compared to Ti50Pt50 alloy. However, partial substitution of Ni with Pt in TiNi alloys results in high temperature transformation properties and the ability to perform work under relatively high stress conditions at high temperatures [12].…”
Section: Introductionmentioning
confidence: 99%